Human Resource Management in the AI Era: Challenges and Opportunities - Aris Sarjito (PT FORMOSA CENDEKIA GLOBAL, 2023)
This qualitative research explores the use of Artificial Intelligence (AI) in Human Resource Management (HRM) and its implications. This study investigates specific areas in HRM where AI is currently being applied and its potential for the future. Ethical considerations, skill requirements, and impact on traditional HR practices are examined as challenges in integrating AI. Additionally, this research explores how AI can improve HRM processes, including efficiency, decision making, and employee experience. Strategies for HR departments to mitigate AI-related challenges while maintaining a harmonious blend of technology and human touch are also discussed. Employees' perceptions, concerns and expectations regarding the integration of AI in HR processes were also analyzed. The study concludes by highlighting the importance of adapting HR practices to the AI ​​era and harnessing the potential of AI for HR improvement.